Clinical Manifestations of Infants with Vitamin B12 Deficiency due to Maternal Deficiency - Meltem Akcaboy Ileri; Baris Malbora; Saliha Senel (Mediterranean Journal of Hematology and Infectious Diseases)
Background: Human species does not synthesize vitamin B12. In developing countries, vitamin B12 deficiency in infants due to maternal diet without adequate protein of animal origin has some characteristic clinical and laboratory features. We report our cases that admitted to hospital with different clinical presentations by the need of hospitalization but have the diagnosis of vitamin B12 deficiency in follow-up and evaluation.